Postmarketing studies for novel drugs approved by both the FDA and EMA between 2005 and 2010: a cross-sectional study. Issue 12 (21st December 2017) - Zeitoun, Jean-David; Ross, Joseph S; Atal, Ignacio; Vivot, Alexandre; Downing, Nicholas S; Baron, Gabriel; Ravaud, Philippe
Abstract : Objectives: To characterise postmarketing studies for drugs that were newly approved by the US Food and Drug Administration and the European Medicines Agency. Design and setting: Cross-sectional analysis of postmarketing studies registered in ClinicalTrials.gov until September 2014 for all novel drugs approved by both regulators between 2005 and 2010. Regulatory documents from both agencies were used. Primary and secondary outcome measures: All identified postmarketing studies were classified according to planned enrolment, funding, status and geographical location, and we determined whether studies studied the originally approved indication. Results: Overall, 69 novel drugs approved between 2005 and 2010 were eligible for inclusion. A total of 6679 relevant postmarketing studies were identified; 5972 were interventional (89.4%). The median number of studies per drug was 55 (IQR 33–119) and median number of patients to be enrolled per study was 60 (IQR 28–183). Industry was the primary sponsor of 2713 studies (40.6%) and was a primary or secondary sponsor in 4176 studies (62.5%). In all, 2901 studies (43.4%) were completed, 487 (7.3%) terminated, 1013 (15.2%) active yet not recruiting, 1895 (28.4%) recruiting and 319 (4.8%) not yet recruiting. A total of 80% of studies were conducted in only one country and 84.4% took place in Europe and/or North America; 2441 (36.5%) studied another indication than the originally approved indication. Studies designed in the originally approved indication were found to be more industry-sponsored than others 68.7%vs53.7%; P<0.0001. Conclusions: Postmarketing pharmaceutical research was highly variable and predominantly located in North America and Europe. Postmarketing studies were frequently designed to study indications other than the originally approved one. Although some findings were reassuring, others question the lack of coordination of postmarketing research.